2013
DOI: 10.1590/s1516-35982013000600007
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass traits of Santa Inês lambs finished with different sources of forage

Abstract: -The objective of this study was to evaluate performance and biometrics of lambs fed different sources of forage. Twenty-four six-month-old Santa Inês female lambs were randomly allocated to four experimental diets and housed in individual stalls. They weighed on average 26.35±0.20 kg. The diets were coast cross hay (HAY), cassava hay (CAS), dehydrated by-product of pea crop (PEA) and saccharin (SAC). The diets were formulated with the same amount of protein and energy with fixed levels of forage (60%) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
3
4
0
Order By: Relevance
“…It was observed that animals which had a higher final body weight tended to record higher weights for the commercial cuts (leg, shoulder, neck, belly), as expected. This result agrees with Menezes et al (2013) who demonstrated that carcass yield increased with body weight. However, the development of organs showed different growth stages, as each animal reached maturity at different physiological ages (Carvalho et al, 2016).…”
Section: Fatty Acid Profile Levels Of Replacementsupporting
confidence: 93%
See 2 more Smart Citations
“…It was observed that animals which had a higher final body weight tended to record higher weights for the commercial cuts (leg, shoulder, neck, belly), as expected. This result agrees with Menezes et al (2013) who demonstrated that carcass yield increased with body weight. However, the development of organs showed different growth stages, as each animal reached maturity at different physiological ages (Carvalho et al, 2016).…”
Section: Fatty Acid Profile Levels Of Replacementsupporting
confidence: 93%
“…The weight loss by cooling (2 %) was not affected by the diet and was similar to those observed by other authors working with alternative foods for sheep (Menezes et al, 2013). Overall, subcutaneous fat deposition (average of 2.97 mm) did not differ in lambs fed different dietary treatments.…”
Section: Fatty Acid Profile Levels Of Replacementsupporting
confidence: 87%
See 1 more Smart Citation
“…As there were no differences in nutrient digestibility between genetic groups, the higher rumination efficiency observed in Santa Inês lambs is probably due to anatomical and/or physiological differences between genetic groups. Considering that the ruminal passage rate is higher in Dorper (Moyo and Nsahlai 2018) and lower in Santa Inês lambs (Menezes et al 2013), the latter needs to ruminate a higher amount of material to be able to empty the rumen, resulting in a higher amount of dry matter ruminated per unit of time. Furthermore, the trend on PC digestibility probably is the result of a more efficient ruminal microbiota in Santa Inês lambs.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the tissue composition of the carcass, the most used technique is dissection of the basic components of the animal's body, but this technique is extremely slow and costly, in addition to the need to dispose of the carcass. An alternative method for assessing tissue composition, to avoid complete dissection of the carcass, is the dissection and chemical analysis of the 12 th rib, which simplifies the processing of samples due to the lower demand for tissues for evaluation, in addition to presenting high correlations with the various carcass components (Menezes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%